THE EFFECT OF EDUCATION AND TRAINING, WORK ENVIRONMENT AND SUPERVISION TO TEACHER PERFORMANCE IN JUNIOR HIGH SCHOOL STATE 1 TERAS BOYOLALI - Ade Fitri Febri Romadhani; Nani Irma Susanti (KELOLA, 2019)
The purpose of this research was to study education and training, work environment and supervision of teacher performance in Teras 1 Junior High School. This research is census research. With a sample of 37 respondents. Data analysis methods related to validity test, reliability test, t test, F test and R2 test. The results of the t test are as follows: significant education and training variables on teacher performance, significant work environment on teacher performance, significant supervision of teacher performance. The F test results simultaneously variables of education and training, work environment and supervision, positive and significant to teacher performance. Teacher performance is explained by variables of education and training, work environment and supervision totaling 35.2% while the remaining 64,8% are explained by other variables which was not included in the study sucj as work motivation, job satisfaction, organizational culture ands competence.